Confidentiality in Childbirth Education - Philipsen, Nayna C. (Lamaze International Inc., 2010)
Protecting the confidentiality of the personal information that childbirth educators receive from their clients is crucial. Without this respect for privacy, educators will not be able to get the information essential to meeting their objectives. Childbirth educators who work in schools may come under federal law that protects individual student records (Family Educational Rights and Privacy Act, or FERPA). Childbirth educators who are employed in a health-care facility may come under federal law that protects individual health information (Health Insurance Portability and Accountability Act, or HIPAA). All childbirth educators must be thoughtful advocates of the rights to privacy and self-determination of expectant parents.